Characterization of Iron III Oxyhydroxides in Hydrometalllurgical Residues - Loan, Mitch; Richmond, William; Hockridge, James; Hart, Robert; Farrow, John; Parkinson, Gordon; St. Pierre, T.; Newman, M. (The Minerals, Metals and Materials Society, 2005)
The characterization of iron iii oxyhydroxides arising from neutralization (removing dissolved iron and/or impurities), or precipitation in storage ponds, mine drainage and waste streams (oxidization of dissoved Fe ii) can prove difficult. The low solubility of iron iii inherently creates a high supersaturation environment favoring the formation of nanoscale, poorly crystalline, and metastable phases. These often have poor physical properties - controlling the properties of the residue - and contain high loadings of important adsorbed components. In this manuscript we provide examples of iron iii oxyhydroxide characterization from hydrometallurgical residues and more synthetic-based studies. We detail techniques to help delineate differences between poorly crystalline iron iii oxyhydroxides (2- and 6-line ferrihydrite, schwertmannite, akaganeite and goethite), and more combinational approaches for when admixed in heterogeneous residues. Generally, identification and even quantification can be achieved with a higher degree of confidence than by use of a single technique such as X-ray diffraction (XRD)